On Integration-by-parts and the Itô Formula for Backwards Itô Integral - Cabral, Emmanuel A (Archīum Ateneo, 2011)
In this paper, we derive integration-by-parts for-mula using the generalized Riemann approach to stochastic calculus called the backwards Itô integral. Moreover, we use integration-by-parts formula to deduce the Itô formula for the backwards Itô integral.